The Effects of Withdrawal Stop Duration in the Directional Solidification of Al-7 wt% Si Alloy on Solidification Parameters, Microstructure, and Microhardness - Seab Piseth; Dedy Masnur (Departmen Teknik Mesin dan Industri, Fakultas Teknik, Universitas Gadjah Mada, 2020)
The effects of withdrawal stop duration in the directional solidification of Al-7 wt% Si alloy on solidification parameters, microstructure, and microhardness were investigated. Directional solidification experiments were carried out in five stopping durations: 0 s, 20 s, 30 s, 40 s, and 50 s. Some solidification parameters such as growth rate and temperature gradient were calculated in the stopping region 15 mm from the bottom of the sample. Microstructure parameters such as primary and secondary dendrite arm spacings were defined on both longitudinal and transverse sections in the stopping region, whereas microhardness properties were tested on the longitudinal section in this region. With the rise in the withdrawal stop duration from 0 s to 50 s, the growth rate decreased slightly from 1.26 to 0.84 mm/s, while the temperature gradient remained at 1.71 ˚C/mm. Furthermore, the microstructure of α-Al dendrites became coarser, and their shapes changed from thin to irregular plates. Primary and secondary dendrite arm spacings increased from 106.4 to 205.7 µm and 19.4 to 38.1 µm, respectively, when the stopping duration was increased. In addition, the hardness decreased from 54.0 to 49.9 HV.